Effects of Muscle Energy Technique versus Shoulder Mobilization on Pain and Function in Patients with Subacromial Pain Syndrome - Ishaq, Shahid; Dustgir, Atif; Mehdi, Zunaira; Mahmood, Khalid; Fatima, Rukhsar; Tasawer, Muhammad Noman (physioscience, 2023)
Background Subacromial pain syndrome is most leading cause of disability that includes the wide spectrum of disorders including subacromial tendinopathy, partial or full thickness tear of rotator cuff and subacromial bursitis. The manual therapy interventions for this condition are still debatable.Aim To evaluate the comparative effects of muscle energy technique (MET) versus posterior shoulder mobilization with movement (MWM) on pain, function and shoulder range of motion in patients with subacromial pain syndrome.Method Patients diagnosed with subacromial pain syndrome were recruited in this pragmatic parallel double blinded randomized clinical trial. The sample was selected through non-probability convenient sampling technique. Forty patients out of 56 meeting the eligibility criteria were equally divided into two groups, MET group (n = 20) and MWM group (n = 20), through a randomization web service. Data were collected at baseline and after successful completion of a six week trial treatment. Pain severity was measured by using a numeric pain rating scale, shoulder disability was measured by using the Shoulder Pain and Disability Index (SPADI) and ranges of motion were measured by using goniometry. Data was analyzed through SPSS 24.Results Outcome measures including pain, disability and shoulder range of motion were significantly (p ≤ 0.05) improved in both groups after the intervention. When comparing both groups, pain score was U = 82.0 (p ≤ 0.001) and disability score was t = –2.913 (p ≤ 0.006) favoring MET.Conclusion Both MET and MWM were effective for symptomatic management in this sample of 40 patients with subacromial impingement syndrome. MET seems to show some superior effects as compared to MWM.
Keywords: muscle energy technique; mulligan mobilization; shoulder disability; shoulder mobilization; shoulder pain syndrome